CPT-11-Induced Delayed Diarrhea Develops via Reduced Aquaporin-3 Expression in the Colon - Risako Kon (International Journal of Molecular Sciences, 2018)
While irinotecan (CPT-11) has a potent anti-cancer effect, it also causes serious diarrhea as an adverse reaction. In this study, we analyzed the pathogenic mechanism of CPT-11-induced delayed diarrhea by focusing on water channel aquaporin-3 (AQP3) in the colon. When rats received CPT-11, the expression level of AQP3 was reduced during severe diarrhea. It was found that the expression levels of inflammatory cytokines and the loss of crypt cells were increased in the colon when CPT-11 was administered. When celecoxib, an anti-inflammatory drug, was concomitantly administered, both the diarrhea and the reduced expression of AQP3 induced by CPT-11 were suppressed. The inflammation in the rat colon during diarrhea was caused via activated macrophage by CPT-11. These results showed that when CPT-11 is administered, the expression level of AQP3 in the colon is reduced, resulting in delayed diarrhea by preventing water transport from the intestinal tract. It was also suggested that the reduced expression of AQP3 might be due to the inflammation that occurs following the loss of colonic crypt cells and to the damage caused by the direct activation of macrophages by CPT-11. Therefore, it was considered that anti-inflammatory drugs that suppress the reduction of AQP3 expression could prevent CPT-11-induced delayed diarrhea.